Welfare reform in Southern Europe under Austerity. Institutional heterogeneity and change - González Begega, Sergio; Guillén Rodríguez, Ana M. (Papeles de Europa, 2018)
The focus of this research note is to assess comparatively recent institutional change in Southern European welfare states. The outbreak of the financial and economic crisis in 2008 triggered a new scenario for welfare reform. Social protection systems were forthwith brought to a major transformation juncture under high political and economic strain. The political response to the crisis brought about austerity in public expenditure and harsh institutional reshaping of welfare provisions in order to regain fiscal consolidation, solvency of the public sector and external competitiveness. The outcome of austerity measures has been an increasing differentiation in the pace and process of institutional reform within the Mediterranean welfare model.
Keywords: Welfare state; social protection; Southern Europe; austerity.